Practicing Teachers’ Use of Online Tools for IEP Goal Writing and Instructional Support - Dunn, Michael; Rice, Mary (Journal of the American Academy of Special Education Professionals, 2022)
This study investigated special educators’ perspectives about an online toolkit that offers teachers example goals and objectives statements to use in service plans for students with special educational needs as well as teaching strategies and assessments. Special education teachers in a large school district in a Pacific Northwestern state answered a short survey (n=19). Some respondents also participated in group interviews (n=6). The research questions were: what are special education personnel’s perspectives about the online toolkit materials for writing goals and objectives for children with special educational needs; and, what do special education personnel perceive to be online toolkit’s limitations as well as weaknesses? Results indicated that the participants preferred to use the online toolkit for identifying initial ideas for goals and objectives statements in the disability service plans. However, the teachers desired more professional learning and collegial dialogue to learn about instruction, strategies, and assessment tools. The authors also discuss implications and suggested next steps for online tools in professional learning for teachers.